AN ANALYSIS OF ENGLISH TEACHERS WRITTEN FEEDBACK IN PRIMARY STUDENTS REPORT CARDS - Widyastuti, Pauline; Pramono, Y.G. Harto (LLT Journal: A Journal on Language and Language Teaching, 2021)
This study analyzed teachers written feedback to explore how well the teachers written feedback corresponded to the principles of evaluation and the extent to which their written feedback was aligned with the students numerical scores in the report cards. This study collected 112 written feedback from 5 teachers and the corresponding numerical scores in the students report cards from one of the private Primary Schools in Surabaya. The teachers written feedback was analyzed based on the principles of evaluation. The results of the analysis indicated that none of the teachers wrote feedback which met the criteria of an ideal feedback covering praise, criticism, and suggestion equally at the same time. All teachers only gave praise mostly to very good and excellent students; they almost never gave criticism and suggestion to them. To the low achieving students, the teachers mostly gave criticism and suggestion, and almost never gave any praise. In regard to the alignment between the teachers written feedback and the students numerical scores in the report cards, the finding indicated that the teachers written feedback was well aligned with the students numerical scores.